HIV-1 genetic diversity and its distribution characteristics among newly diagnosed HIV-1 individuals in Hebei province, China. Issue 1 (December 2016) - Lu, Xinli; Zhao, Cuiying; Wang, Wei; Nie, Chenxi; Zhang, Yuqi; Zhao, Hongru; Chen, Suliang; Cui, Ze
Abstract Background Since the first HIV-1 case in 1989, Hebei province has presented a clearly rising trend of HIV-1 prevalence, and HIV-1 genetic diversity has become the vital barrier to HIV prevention and control in this area. To obtain detailed information of HIV-1 spread in different populations and in different areas of Hebei, a cross-sectional HIV-1 molecular epidemiological investigation was performed across the province. Methods Blood samples of 154 newly diagnosed HIV-1 individuals were collected from ten prefectures in Hebei using stratified sampling. Partialgag andenv genes were amplified and sequenced. HIV-1 genotypes were identified by phylogenetic tree analyses. Results Among the 139 subjects genotyped, six HIV-1 subtypes were identified successfully, including subtype B (41.0 %), CRF01_AE (40.3 %), CRF07_BC (11.5 %), CRF08_BC (4.3 %), unique recombinant forms (URFs) (1.4 %) and subtype C (1.4 %). Subtype B was identified as the most frequent subtype. Two URF recombination patterns were the same as CRF01_AE/B. HIV-1 genotype distribution showed a significant statistical difference in different demographic characteristics, such as source (P < 0.05), occupation (P < 0.05) and ethnicity (P < 0.05). The distributions of subtype B (P < 0.05), CRF01_AE (P < 0.05), CRF07_BC (P < 0.05) and subtype C (P < 0.05) showed significant differences in all ten prefectures, and the distributions of all six subtypes were significantly different in Shijiazhuang (P < 0.05) and Xingtai (P < 0.05), but not in other prefectures (P > 0.05). The differences in HIV-1 genotype distribution were closely associated with transmission routes. Particularly, all six subtype strains were found in heterosexuals, showing that HIV-1 has spread from the high-risk populations to the general populations in Hebei, China. In addition, CRF01_AE instead of subtype B has become the major strain of HIV-1 infection among homosexuals. Conclusions Our study revealed HIV-1 evolution and genotype distribution by investigating newly diagnosed HIV-1 individuals in Hebei, China. This study provides important information to enhance the strategic plan for HIV prevention and control in China.